Hyponatraemia as the leading symptom of tuberculous meningitis in a 14-month-old girl - Błaszczyk, Ewa; Firek-Pędras, Małgorzata; Sordyl, Joanna; Berdej-Szczot, Elżbieta; Machnikowska-Sokołowska, Magdalena; Gruszczyńska, Katarzyna; Czerwińska, Ewa (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Tuberculous meningitis (TBM) is a rare form of tuberculosis (TB), however can lead to severe neurological deficits or even to death. TBM remains a diagnostic challenge because of nonspecific symptoms and subacute course. However, it is worth remembering hyponatraemia is a relatively common symptom in neuroinfections, especially in TBM. We report the case of 14-month-old girls admitted to hospital with fever, vomiting and loose stools, with persistent laboratory hyponatraemia. Despite the initial lack of specific symptoms and history suggesting contact with person suffering from TB, the TBM was recognized in the first phase of the disease before evident symptoms of the central nervous system.